Сareer anchors and organizational commitment in generations’ perspective: an overview of the literature - Tairova, K. T.; Tazhina, G. O. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2020)
Abstract. Issues of career preferences are tangible theoretical and practical concerns of any society. From the viewpoint of the Generations Theory, the representatives of X, millennials and the baby boomer generations are currently the productive societal job-force. The trajectory and development of their professional career is determined by the degree of reciprocity between the personality psychological potential and the content and requirements of professional activity, including the extent of employee’s organizational commitment. In this paper, we provide an overview of the research pertaining to career preferences/anchors and organizational commitment in major workforce generations’ perspective. The literature review was conducted using a variety of databases and sources were broadly centered around the following issues: career anchors and those of different generations; generations’ perceptions of organizational commitment; how career anchors and organizational commitment are interrelated. The reviewed articles were grouped within each issue using the authors’ findings to analyze gaps in the research. Key words: career anchors, organizational commitment, generation X, Millennials, baby boomers.